Association of vitamin D receptor gene polymorphism (rs10735810) and chronic periodontitis - Murthykumar, Karthikeyan; Arjunkumar, Radhika; Jayaseelan, Vijayashree Priyadharsini (Journal of investigative and clinical dentistry, 2019)
The aim of the present study was to analyze the association between vitamin D receptor (VDR) (rs10735810) gene polymorphism and chronic periodontitis (CP). A total of 100 subjects were recruited for this study, which included 50 CP and 50 healthy controls. Genomic DNA was extracted from the whole blood collected from the subjects. DNA was amplified using specific primers flanking the FokI region of the VDR gene (rs10735810). The amplicon was further subjected to genotyping using restriction fragment length polymorphism (RFLP) using the FokI enzyme. The genotype obtained based on RFLP pattern was recorded and used for statistical analysis. The distribution of genotypes and allele frequencies in the chronic periodontitis and control groups were compared using the χ -test. The CP group displayed the highest frequency of CT (20%) and TT (6%) genotypes when compared with the control subjects. Allele frequency was found to be similar in both groups. The C allele was found to be predominant in the study population compared with the T allele. The present study denotes that the VDR polymorphism (rs10735810) is not associated with CP in the study group analyzed.